M cell–dependent commensal uptake confers encephalitogenic phenotypes on γδT17 cells in Peyer’s patches - Seiga Komiyama; Yotaro Kodaira; Rae Maeda; Yuki Sugiura; Koichiro Suzuki; Aiko Saeki; Yusuke Kinashi; Hiroyuki Oguchi; Kokona Takano; Satoshi Onawa; Ako Matsui; Eita Sasaki; et al. (Proceedings of the National Academy of Sciences, 2026)
Interleukin-17-producing γδT cells (γδT17 cells) play a dual role in immune regulation, serving as both protectors in various tissues and orchestrators of inflammatory responses in autoimmune diseases, including experimental autoimmune encephalomyelitis (EAE), a rodent model of multiple sclerosis. However, the ontology and repertoires of encephalitogenic γδT17 cells remain unclear. In this study, we demonstrate that the encephalitogenicity of γδT17 cells is conferred through microfold cell (M cell)-dependent uptake of commensal bacteria in Peyer’s patches. Specifically, CXCR6 hi Vγ6 + Vδ1 + invariant γδT17 cells are activated by specific commensal bacteria such as Lactobacillus spp., which stimulate TCR of CXCR6 hi Vγ6 + Vδ1 + invariant γδT17 cells. During the early stages of EAE, γδT17 cells infiltrate the central nervous system (CNS), initiating a type 17 inflammatory response. Our findings illustrate that Peyer’s patch M cells serve as a critical bridge, linking the pathological association between commensal bacteria and the onset of CNS inflammation.